A conceptual framework for ecologically and socially sustainable land management and agricultural development in Africa. (15th September 2006) - Eze, Eze Bassey; Neba, Ndenecho Emmanuel
Agricultural development in Sub-Saharan Africa witnessed an initial period of growth in the few years after independence (1960s) and went into decline after the 1980s. This spurred many governments to embark on structural adjustment programmes that are only just showing the first signs of improvement. This raises some searching questions concerning the process of formulating and implementing reforms with a long-term vision of sustainable agricultural development in the continent. Drawing from past experiences, this paper explores the conceptual framework needed to achieve ecologically and socially sustainable agriculture in Africa. This paper argues that conventional agriculture has been severely limited by its disciplinary and reductionist approach. Despite the usefulness of modern agricultural technologies and insights, they have been applied in isolation and without sufficient concern for the indigenous knowledge-base of farmers and for ecological effects, which has rendered them debatable and sustainability unattainable. This paper, therefore, elaborates a holistic framework, which integrates various scientific disciplines, ecologically oriented and People-Centred Agricultural Development (PCAD) principles for achieving long-term impacts and sustainability under changing socio-economic, political and ecological framework conditions.